2010
DOI: 10.1016/j.sleep.2009.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported sleep disturbances during cannabis withdrawal in cannabis-dependent outpatients with and without opioid dependence

Abstract: A cannabis withdrawal syndrome (at least two symptoms) occurs in more than 50% of dependent smokers after cessation (1). The typical withdrawal pattern is composed of 6 symptoms: anger or aggression, decreased appetite or weight loss, irritability, nervousness/ anxiety, restlessness, and sleep difficulties (1). The rate of sleep disturbances during cannabis cessation was found to be 32% in non-treatment seeking dependent smokers (2). The two most frequent sleep symptoms are reduced sleep duration and strange o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 5 publications
(6 reference statements)
1
11
0
Order By: Relevance
“…As noted above, the desirable effects of cannabis on sleep are reported less frequently in chronic cannabis users compared to naïve users [ 91 ], Chronic users also report difficulty sleeping and strange dreams among other symptoms associated with abstinence [ 11 , 28 , 43 , 58 , 175 , 194 ]. These subjective findings have been correlated to longer sleep onset latency, reduced slow-wave sleep, and REM rebound observed in PSG studies [ 27 , 198 ].…”
Section: Cannabismentioning
confidence: 85%
“…As noted above, the desirable effects of cannabis on sleep are reported less frequently in chronic cannabis users compared to naïve users [ 91 ], Chronic users also report difficulty sleeping and strange dreams among other symptoms associated with abstinence [ 11 , 28 , 43 , 58 , 175 , 194 ]. These subjective findings have been correlated to longer sleep onset latency, reduced slow-wave sleep, and REM rebound observed in PSG studies [ 27 , 198 ].…”
Section: Cannabismentioning
confidence: 85%
“…We screened a total of 3848 unique citations, of which 86 were screened in full, and 47 were included in the review (Figure 1), reporting on 50 unique cohorts. In total, 23 518 participants were 32,47,52 the Customary Drinking and Drug Use Record, 50 the Composite International Diagnostic Interview-Substance Abuse Module, 17,20,25,30,36,39 the Cannabis Withdrawal Scale, 37,51,54,56 the Marijuana Quit Questionnaire, 28,41,43,45,46,58 the Marijuana Withdrawal Symptom Checklist, 6,7,27,33,34,42,49,53,55,60 the Semi-Structured Assessment for the Genetics of Alcoholism, 18,40,48 the Structured Clinical…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the cannabis withdrawal syndrome has not yet been studied in poly-substance using patients with the exception of one small cross-sectional study by Vorspan and colleagues that indicated that sleep disturbances, but not other cannabis withdrawal symptoms, were exacerbated in patients with co-morbid opioid dependence [ 26 ]. Arguably, there are good reasons for the omission of poly-substance using patient samples when establishing the validity and time course of the cannabis withdrawal syndrome.…”
Section: Introductionmentioning
confidence: 99%